Strategi Kepala Madrasah dan Guru dalam Meningkatkan Prestasi Peserta Didik - Adhwa'Lu'lu'ah Qurrotul’ain; Atim Rinawati; Benny Kurniawan (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to analyze the implementation strategies of Madrasah Principalsand Teachers in improving student achievement and explain the driving andinhibiting factors of Madrasah Principals and Teachers' strategies in improvingstudent achievement at Madrasah Ibtidaiyah Ma'arif Depokrejo. This study uses aqualitative approach by processing the data obtained in the field. The researchsubjects were the Head of Madrasah, Teachers, and students at MadrasahIbtidaiyah Ma'arif Depokrejo. The research strategy used is to use data collectiontechniques through observation, interviews, discussions, and document studiesand perform data analysis with data reduction, data presentation and then take dataverification. The results of the study found that the implementation of the Head ofMadrasah and Teachers, students of grades IV, V and VI of Madrasah IbtidaiyahMa'arif Depokrejo were in the stage of habituation. The driving factors inimplementing the Principal and Teacher Strategy are: (1) creative, (2) innovative,and (3) LCD, while not encouraging include: (1) morning until noon in Madrasah,(2) self-employed, (3) attention to children, (4) socializing, and (5)communicating